Specific components found in circulating immune complexes (CIC) in paracoccidioidomycosis - Unterkircher, C. S. [UNESP]; Yazaki, S. C. [UNESP]; Shimizu, M. T. [UNESP]; Jorge, A. O C [UNESP]; Camargo, Z. P. (Oxford University Press (OUP), 1996)
Circulating immune complexes (CIC) from 15 paracoccidioidomycosis (PCM) patient sera and from 20 healthy control sera were analysed. After CIC precipitation, solubilization and acid treatment, only a little reactivity to P. brasiliensis antigens was found in the free antibodies from PCM-CIC. This result has suggested that there were antibodies with a high affinity bound to fungus components. Dissociated CIC were fractionated in a column of Sephacryl S300 and the fractions that probably contained antigens were pooled and applied to an affinity column, prepared with mouse anti-gp43 monoclonal antibody. Using ECL-Western blotting assay two polypeptide with apparent mass of 43 and 62 kDa were found.
Keywords: adult; aged; antibody affinity; antibody detection; antigen antibody complex; clinical article; female; human; immunoblotting; male; south american blastomycosis; Adult; Aged; Animals; Antibodies, Fungal; Antibodies, Monoclonal; Antigen-Antibody Complex; Antigens, Fungal; Humans; Immunoglobulin G; Immunoglobulin M; Mice; Middle Aged; Paracoccidioidomycosis; Reference Values; Fungi; paracoccidioidomycosis brasiliensis